Disorientation effects, circulating small ribonucleic acid, and genetic susceptibility on static postural stability. Issue 3 (March 2023) - Turner, Ashley; Markey, Michael; Le, Peter; Reiter, Ali; Cox, Cyndy; Simmons, Stacy; Rao, M.B.; Altman, Lorenna; Davis, Kermit; Huber, Dustin; Dufour, Jonathan S.; Marras, William; et al.
Abstract: Background: Motion Sickness increases risk of performance deficits and safety of flight concerns. The etiology of motion sickness is poorly understood. Here, we attempted to quantify the physiological effects of motion sickness on static balance and determine the genetic predictors associated with these effects. Methods: 16 subjects underwent a disorientation stimulus to induce motion sickness. Motion sickness susceptibility was identified using the Motion Sickness Susceptibility Questionnaire. Postural balance outcomes were measured using two tasks, and small ribonucleic acid profiles were assessed with blood draws before motion sickness stimulus. Differences in postural sway before and after the stimulus as well as effect modification of susceptibility were assessed. A random forest followed by regression tree analysis was constructed for each postural sway variable to determine top genetic and covariate predictors. Findings: Significant differences existed in mean postural balance responses between before and after stimulus. Individuals with longer stimulus survival experienced a greater (but insignificant) perception of sway, even if not displaying increased sway for all conditions. Circulation small ribonucleic acids were differentially expressed between individuals with long and short stimulus survival, many of these microRNA have purported targets in genes related to vestibular disorders. Interpretation: We found motion sickness produces transient motor dysfunction in a healthy military population. Small ribonucleic acids were differentially expressed between subjects with long and short stimulus survival times.